Profile of Creative Thinking Skills of S1 Chemistry Students On The Topic of DNA Isolation Using Project Based Learning (PJBL) - Dewi Agustiani Zulfifah; Florentina Maria Titin Supriyanti; Wawan Wahyu (Jurnal Syntax Transformation, 2023)
This study aims to obtain information about creative thinking skills in students through the application of the project based learning (PjBL) model on the topic of DNA isolation. The research method used is mixed-method embadded with One Group Pretest-Posttest pre-experimental research design. A limited trial was conducted on 33 chemistry education study program students at one of the State Universities in Bandung. The instruments used in this study are structured description and MFI problems. Data analysis using pretest and posttest values using the N-Gain equation <g> and obtaining the percentage of MFI values per group. The results of the creative thinking assessment showed that the N-gain value obtained was 0.78 with a high category. Other results from this study obtained percentage values on each indicator of creative thinking skills including flexibility thinking skills (flexibility) 87.88%, fluent thinking (fluency) 93.94%, original thinking (originality) 85.95% thinking elaboration (elaboration) 87.88%, Thinking evaluation (evaluation) 93.94% with a very good category after students carry out learning with the PjBL model can improve students' creative thinking skills on the topic of fruit DNA isolation.